Assessment of knowledge process capabilities toward project management maturity: an empirical study - Alghail A.; Yao L.; Abbas M.; Baashar Y. (Emerald Group Holdings Ltd., 2023)
Purpose: The reasons behind the project management failure of higher education institutions (HEIs) have been researched for the past few years. One of the reasons is the lack of tools to integrate their knowledge process capabilities (KPC) with their project management (PM) to measure maturity by assessing these capabilities. Various project management maturity (PMM) models exist. Yet, there is a limited number of empirical studies that support the four integrations of KPC and PMM. Therefore, this study aims to propose a new heretical model, namely, KPC-knowledge management (KM) and evaluates a research model that includes the four KPC as an antecedent to PMM. Design/methodology/approach: The suggested research model is assessed by using partial least squares structural equation modeling. Furthermore, the study's hypotheses were examined based on a sample of 352 respondents from the project management departments in 10 public universities in Yemen. Findings: Analysis revealed that the derived PMM status could be benchmarked with the project management maturity model. Also, the study found that integrating the KPC into PM enables the institutions to perform critical tasks and value chain activities and enhance the PM maturity level as well. In contrast, if one of the capabilities does not positively impact PMM, it affects the maturity level of the entire project. Research limitations/implications: The findings are obtained concerning data collected from public universities and represent the Yemeni context, limiting the generalization on a different geographical area. Also, this proposed model can be evaluated in a practical way like conducting a focus group, a set of interviews with specialists, a case study or action research. The qualitative research will help academics to validate our proposal for future research purposes. Practical implications: The proposed approach may be adapted to the characteristics of organizations involved in projects as external performers (project-based organizations) and not just the HEIs projects. This study provides managers and policymakers with insights into assessing PMM and improving their organizational effectiveness when deciding which KPCs to focus on in the future. Social implications: This study contributes to the current PM awareness in Yemen and facilitates its success using the knowledge processes capabilities in Yemen's HEIs. It encourages organizations to take this opportunity to revive the projects and achieve a maximum level of maturity. Originality/value: This study provides new insights into two domains through the link between knowledge management and PM. To the best of the authors' knowledge, this paper is among the first to empirically study the impact of the four KPC toward PMM. It enriches the theoretical perspective of PM. Also, it contributes to the literature on the success factor of KPC, which can be considered to improve organizational performance. 2021, Emerald Publishing Limited.